Pendampingan Edukasi Cerdas Menyikapi Tren AI (Artifial Intelligence) dalam Dunia Pendidikan - Sahara, Sahara; Ilmi, Miftahul; Silalahi, Rudi Yanto Batara (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This community service activity aims to provide education about the importance of students at Permata Harapan Batam School being smart in responding to the Artificial Intelligence trend. This activity was attended by 33 participants. Delivery of material is carried out using video conferencing, namely using the zoom application. From the results of this service activity, it is known that after participating in this educational activity, it was found that the students of Permata Harapan Batam School stated that this service activity was very useful, in that the students became aware of the skill requirements that must be possessed to be needed in the future in facing the world of work. gain new knowledge and understand the importance of Artificial Intelligence in the current era of digitalization.